2022
DOI: 10.1177/00302228221128156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Emergency Nurses’ Psychological Resilience on Their Thanatophobic Behaviors: A Cross-Sectional Study

Abstract: Purpose This study analyzed the effect of emergency nurses’ psychological resilience on their thanatophobic behaviors. Methods The research was conducted with 156 emergency nurses. In the data collection process, the Socio-Demographic Information Form, the Brief Resilience Scale, and the Thanatophobia Scale were used. Results It was found that emergency nurses had medium-level psychological resilience and high-level thanatophobia. Besides, it was discerned that there was a moderate negative relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…The Thanatophobia Scale mean score of nurses was moderate at 31.74 ± 10.08 in this study. There have been studies in our country examining the thanatophobia levels of nurses and reported moderate to high levels [11,[20][21][22]. In a qualitative study by De Swardt and Fouche (2017), it was determined that nurses who gave post-mortem care to the deceased in the intensive care unit experienced thanatophobia by confronting the reality of their own death [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Thanatophobia Scale mean score of nurses was moderate at 31.74 ± 10.08 in this study. There have been studies in our country examining the thanatophobia levels of nurses and reported moderate to high levels [11,[20][21][22]. In a qualitative study by De Swardt and Fouche (2017), it was determined that nurses who gave post-mortem care to the deceased in the intensive care unit experienced thanatophobia by confronting the reality of their own death [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the nurses' Psychological Resilience Scale for Adults mean score was moderate at 108.34 ± 7.12. A study examining the effect of the psychological resilience of emergency nurses on their thanatophobic behaviours determined that nurses had moderate psychological resilience [22]. There are studies in the literature showing that nurses' psychological exibility is moderate [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los resultados coinciden con los hallazgos del presente trabajo en el cual los profesionales del servicio de Internación conjunta (del área obstétrica) mostraron niveles más altos de resiliencia. Por otro lado, en una muestra de 321 enfermeros de servicios de emergencia, se identificó un nivel de bajo a moderado de resiliencia (18) y en otro trabajo que incluyó una muestra de 156 enfermeras de servicios de emergencia de Turquía el nivel de resiliencia fue moderado (22), contrastando el perfil altamente resiliente en los enfermeros del área de emergencia hallado en el presente estudio.…”
Section: Discussionunclassified